Inventory in Poland - current situation and prospects - Kemp, O. (Land Management, Cadastre and Land Monitoring, 2017)
Poland poddavalsya inventory changes. His origins are taking beginning in late and early vosemnadtsatoho devyatnadtsatoho century, when Polish state zahvatchyky sozdaly The first kadastrovыe otchetы. Austria, Prussia and Russia sozdalytry kadastrovыe system, three yspolzuyuschye system recovery country yzmerenyya.Vo TIME 1918 - 1939 Manuscript kadastrovыe bыly oriented work on the creation edynoy nalohovoy system for vsey territory of the country. After the war bыly zavershenы work. Modernization of the cadastre prodolzhalas in the direction Increase the accuracy and quality of data. At present Time Inventory Accounting vkljuchaet buildings, premises and plots zemelnыh, as well tesno svjazana with zemelnыm registers / ypotekoy.Information, soderzhaschayasya in Nam, everybody yspolzuetsya participants in the control nedvyzhymostyu (surveyors, otsenschykamy, brokers and upravlyayuschymy nedvyzhymostyu, courts and admynystratyvnыmy authorities zanymayuschyhsya territorial-prostranstvennыm Planning).Polskoy origins cadastral area. The first records of kadastrovыh measurement bыly sdelanы 4.5 million. Years ago. Poland was once zaklyuchalas Business surveyor in oblahorazhyvanyy. At the end trynadtsatoho century bыla Created rank post of High - korolevskyy podkamernыy, tasks kotorogoAll selskohozyaystvennыe and lesnыe uhodya bыly ohvachenы oblastyu pochvovedenyya, classification of land osushchestvljaetsja edynoobrazno for vsey country on grounds ofytsyalnoy classes tablytsы land. THIS classification talk at kachestve and soil fertility. Class is determined on a 6-point scale (8 to pahotnыh land). This allows us to Compare Quality of land in any point of the country.By law dolzhna bыt yspolzovana in the Economic Planning and spatial statistics population in sudebnom and administrative razbyratelstve. All ofysы ymeyut access for cadastre data bases online free. Chastnyya Faces and company mogut Require info sobstvennoy REAL ESTATE otdelnuyu for a fee.Inventory tesno svjazana with systemoy zemelnыh reestrov / ypotekoy. Ymeyte in mind, something cadastre That was the main thing tselju Introduction tax. Therefore on rehystryruet realnoe tekuschye STATUS (for example: at present aktualnoe Using Time zemelnыh plots, current availability sobstvennyka REAL ESTATE (for example, naslednyk, kotoryya not Finished zakonnыe protsedurы pravopreemstva) or How THIS neobhodyma info nachyslenyya for payment.Kadastrovыy 3D. At the level of research provodytsya the Scientific Search of opportunities for the creation of 3D-cadastre.Inventory in Poland ymeet davnye traditions. In many techenye desyatyletyy, yzmenylys hosudarstvennыe regimes and topics yzmenylsya Together with inventory and ego role in the economy of the state. At present pervychnoyzadachey cadastre TIME REAL ESTATE - creation of a system of tax collection from REAL ESTATE - javljaetsja vtorostepennыm task. WARNING Prynymaya t Volume sobrannoy of information, .ee pravdopodobnost and accuracy, and First Total globality, the main thing remains Relevance role dannoy information.The inventory constantly razvyvaetsya. Poland, on vedetsya in digital forms and is believed Samoa Large data base REAL ESTATE. THIS data base constantly menyaetsya. Some IZ potentsyalnыh already Modified hotovы for Implementation (The cost of property tax on) Some partially voshly (3D cadastre) as part nekotoraya everything else before a Stage issledovatel`skoe work (mnohotselevoy inventory).Keywords:  cadastre, 3D cadastre, a multi-purpose cadastre, the cadastral value.